2014
DOI: 10.1186/1471-2458-14-1073
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder and its risk factors among adolescent survivors three years after an 8.0 magnitude earthquake in China

Abstract: BackgroundSerious and long-lasting psychiatric consequences can be found in children and adolescents following earthquake, including the development of posttraumatic stress disorder (PTSD). Although researchers have been focused on PTSD recently, its prevalence and risk factors after a huge natural disaster are still unclear because of limited sample size. The purpose of this study is to explore the prevalence of posttraumatic stress disorder (PTSD) in adolescent survivors three years after the Wenchuan earthq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
2
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 22 publications
4
41
2
7
Order By: Relevance
“…In the present study, the probability of PTSD after the Wenchuan earthquake was relatively lower than reports in other studies. Specifically, the probability of PTSD ranged from 15.9 to 36.5% among children in some studies conducted from three months to three years after the Wenchuan earthquake (Fan, Zhang, Yang, Mo, & Liu, 2011; Hou et al, 2011; Pan et al, 2015), which was higher than the probability obtained in our study, whereas the probability of PTSD one year later (5.6–8.7%) found in other studies was similar to our result (Lin et al, 2013; Tian, Wong, Li, & Jiang, 2014; Ying, Wu, & Chen, 2013). There were two main reasons for this finding.…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, the probability of PTSD after the Wenchuan earthquake was relatively lower than reports in other studies. Specifically, the probability of PTSD ranged from 15.9 to 36.5% among children in some studies conducted from three months to three years after the Wenchuan earthquake (Fan, Zhang, Yang, Mo, & Liu, 2011; Hou et al, 2011; Pan et al, 2015), which was higher than the probability obtained in our study, whereas the probability of PTSD one year later (5.6–8.7%) found in other studies was similar to our result (Lin et al, 2013; Tian, Wong, Li, & Jiang, 2014; Ying, Wu, & Chen, 2013). There were two main reasons for this finding.…”
Section: Discussionsupporting
confidence: 86%
“…In this study, we noticed that within the three months periods following the earthquake, 27.1% of the respondents met the criteria for a diagnosis of PTSD which was higher than some earthquake studies among adolescents [11][12][13] however lower than the prevalence in other various studies. 4,8,10 A study conducted among Turkish child and adolescent trauma survivors found that almost 60% of Turkish child trauma survivors suffered from moderate to very severe levels of PTSD symptoms even 3 years after the 1999 earthquake.…”
Section: Discussioncontrasting
confidence: 52%
“…In terms of traumatic symptoms and environmental damage conditions, with the exception of kindergartners, children who had their houses damaged or experienced separation from family members had a significantly higher PTSSC-15 score than children who did not experience environmental damage which is unlike from the findings of this study. 13 Significant difference was marked for grade (χ² = 9.324, p<0.01). It signifies that respondents studying in lower grade are more likely to develop symptoms of PTSD than those in higher grade which is similar to a previous study.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The convergence of stresses and traumas, that's regarded as the pre-earthquake experience, peri-earthquake experience and -earthquake experience may lead to the development of post-traumatic stress disorders among the survivors in earthquake affected population. Previous study shows being female, uneducated, and married marital status has been allied with the development of post-traumatic stress disorder (Norris et al, 2008;Sakuma et al, 2015;Tian, Wong, Li, & Jiang, 2014).…”
Section: Introductionmentioning
confidence: 97%